MINERALOGICAL, PHYSICAL, AND CHEMICAL PROPERTIES OF SOILS FROM ANDESITIC VOLCANIC TUFF OF MT. BURANGRANG, WEST JAVA - YATNO, EDI; ZAUYAH, S. (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2003)
Information of soils on andesitic volcanic tuff in Indonesia is still limited. Three soil pedons, formed in andesitic volcanic tuff situated in the intensively cultivated vegetable growing areas and secondary forest areas around the Mt. Burangrang, were studied to understand the physical, chemical and mineralogical properties of these soils. All pedons are located in the middle slope with elevation of about 1000 m above sea level (asl). Bulk and undisturbed soil samples of each horizon were analyzed in the laboratory. The results indicated that all the pedons have very deep solum (> 150 cm), granular to subangular blocky structuresand friable to very friable consistences. Mineralogy of the clay fraction of pedons 2 and 3 is dominated by metahalloysite, whereas large amounts of gibbsite are only present in pedon 1. Mineralogical composition of the sand fraction is predominantly composed of opaque minerals, while weatherable minerals such as hornblende, augite, hypersthene and plagioclase (andesine and labradorite) are present in various amounts. Soil bulk density values are generally less than 0.9 mg m-3. Soil reaction is acid to extremely acid, whereas soil pH NaF is of less than 9.4. Aluminum saturation is high in pedon 3 and upper horizons of pedon 1. Organic carbon contents are generally medium in the surface horizons and decrease with depth. Exchangeable bases are dominated by Ca and Mg in medium to very low amounts, cation exchange capacity is medium to high, and base saturation varies ranging from very low to medium. All the pedons studied do not meet the requirements of andic soil properties (P retention of less than 85%), and are classified as Andic Dystrudepts. Thelow bulk density may contribute to the more favourable soil tilth leading to easy tillage and root development. However, high soil acidity in most soils studied is a limiting factor for plant growth.